The usage of traditional remedies in comparison with medical remedies for the common cold in Al-Medina Al-Munawara - AlBalawi, Haya Zaki H.; Saber, Lobna M.; Khawaji, Nussaiba Yahya N.; AlSibaa, Narjes Mansour A.; AlHarbi, Layan Khalid M.; AlMutairi, Sara Mohammed S. (International Journal of Research in Medical Sciences, 2024)
Background: The common cold, a prevalent viral infection of the upper respiratory tract, often prompts individuals to seek alternative treatments, including herbal and traditional remedies. In Saudi Arabia, herbal medicines, including those with traditional origins, are widespread, reflecting high trust and reliance on these natural remedies. This study aimed to investigate the awareness and use of traditional herbal remedies for treating the common cold in Al-Madinah Al-Munawara, Saudi Arabia, and to compare their effectiveness with conventional medical treatments. Methods: A cross-sectional web-based survey was conducted among 408 individuals aged 18-63 years in Al-Madinah Al-Munawara, Saudi Arabia, from September 2023 to January 2024. A self-administered questionnaire was used to collect data on demographic characteristics, common cold symptoms, and the use of natural products and medications for treating the common cold. The sample size was calculated using OpenEpi version 3, and data were analyzed using SPSS version 27. Results: The results found that traditional and herbal remedies were widely used for treating 230 (56.4%), preventing 67 (16.4%), and enhancing health 59 (14.5%). Along with honey 208 (51.0%) was the most used natural product, followed by guava tea 78 (19.1%), black seed 72 (17.6%), and black cumin 50 (12.3%). Natural products alone were used by 281 (68.9%), while 202 (49.5%) used both medications and natural products. Conclusions: The study found a high prevalence of using traditional herbal remedies, particularly honey, compared to conventional medicines for treating common colds in Al-Madinah Al-Munawara, reflecting cultural significance in Saudi Arabia.